An Industrial Quality Control Study on Relay Electronics Manufacturing, Corp. - Luy, Don Mark (College of Engineering, 2001)
Today, quality is set by the customer. It is meeting and exceeding the customer's expectations and needs. Quality sounds simple, but only the best companies around the world are making these things happen on a daily basis. The objective of the study is to apply the framework of the basic philosophy and and principles of statistical process control in a real-world production system. Relay electronics is a manufacturer of emergency lighting systems, fire alarms, burglar alarms, and PA sound systems. The study focuses on the product which contributes most to the sales revenue of the company, emergency lights and its production process. The researchers documented the existing production process and quality procedures including sampling and inspection plans from raw materials acquisition, work-in-process to finished goods. A process map provides a summary of processes including quality control points and their corresponding checkpoint. Failure modes, effects and criticality analysis was done on a functional level so as to identify critical product failures. After identifying PCB failure as critical, a hardware level FMECA was done to identify critical circuit board components such as relays, diodes and transistors. Major quality problems for the company were identified as follows: 1. Absence of a standardized acceptance sampling plan for raw materials, 2. No records of quality performance indicators such as rework and scrap rates , and 3. No process control of PCB production at testing stage. Problem analysis tools were used to verify failures found to be critical in an FMECA and to find causes for these failures. Prioritization was done and it was found that relays constitute the greatest amount of rework done at this station.